2018
DOI: 10.1083/jcb.201708137
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction via the LINC complex regulates DNA replication in myonuclei

Abstract: Nuclear mechanotransduction has been implicated in the control of chromatin organization and gene expression. Wang et al. show that, in Drosophila myofibers, the LINC complex is required for the regulation of DNA replication and synchronized cell-cycle progression in myonuclei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 86 publications
6
71
3
Order By: Relevance
“…Thus, reduced BAF levels at the nuclear membrane (induced by D-Titin/sls RNAi) correlated with an increase in DNA content (induced by elevated endoreplication) in these myonuclei. Previously, we reported that reduced BAF levels in muscles led to increased DNA levels in the myonuclei (Wang et al, 2018), whereas here we report that specific reduction of BAF at the nuclear membrane is sufficient for promoting increased DNA replication. Taken together these results demonstrate that BAF localization at the nuclear membrane is mechanosensitive, and might repress DNA endoreplication.…”
Section: Baf Localization At the Nuclear Membrane Depends On Proper Ccontrasting
confidence: 73%
See 4 more Smart Citations
“…Thus, reduced BAF levels at the nuclear membrane (induced by D-Titin/sls RNAi) correlated with an increase in DNA content (induced by elevated endoreplication) in these myonuclei. Previously, we reported that reduced BAF levels in muscles led to increased DNA levels in the myonuclei (Wang et al, 2018), whereas here we report that specific reduction of BAF at the nuclear membrane is sufficient for promoting increased DNA replication. Taken together these results demonstrate that BAF localization at the nuclear membrane is mechanosensitive, and might repress DNA endoreplication.…”
Section: Baf Localization At the Nuclear Membrane Depends On Proper Ccontrasting
confidence: 73%
“…Furthermore, this study showed that in the myonuclei of LINC mutant larvae the DNA undergoes additional rounds of DNA replication known as endoreplication, leading to elevated polyploidy (Brayson et al, 2018;Volk, 2012;Wang et al, 2018). These observations implicate the involvement of the LINC complex in the arrest of cell cycle progression in myonuclei of wild-type larvae.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations